Perlindungan Hukum Terhadap Hak Cipta Batik Motif Ceplok Segoro Amarto Di Kota Yogyakarta - Dyah Ayu Widyastutiningrum (Fakultas Hukum Universitas Islam Indonesia, 2019)
Ceplok Segoro Amarto motive batik is a batik with contemporary motives that are protected by copyright obtained automatically or by means of a mechanism for recording copyright. Dekranasda of Yogyakarta City as the copyright holder has moral and economic rights to duplicate and distribute Ceplok Segoro Amarto motive batik as stated in Article 9 of the Copyright Law. Even though it has been protected by copyright, in fact there is still a copyright infringement of Ceplok Segoro Amarto motive batik which is done by piracy by other parties without the permission of the copyright holder in an unlawful manner. This study aims to determine the legal protection of the copyright of the Segoro Amarto Ceplok motive batik as stipulated in Undang-Undang Nomor 28 Tahun 2018 about Copyright. The formulation of the problem posed is: What is the legal protection of the copyright of Ceplok Segoro Amarto Batik motive in the city of Yogyakarta? The results of this study indicate that the Ceplok Segoro Amarto motive batik has been protected by copyright, both obtained automatically because it has been manifested in a tangible form and the motive itself has been recorded in the Ministry of Law and Human Rights. The occurrence of copyright infringement can be submitted to the settlement efforts by resolving through alternative dispute resolution, submitting a claim for compensation to the Commercial Court or filing a criminal claim. This study recommends the need for the Dekranasda of Yogyakarta City and Yogyakarta City Government to make an announcement to the general public that the Ceplok Segoro Amarto batik motif is one of the typical batik of Yogyakarta City and is protected by copyright under Undang-Undang Nomor 28 Tahun 2018 about Copyright.